The Noisy Renaissance : Sound, Architecture, and Florentine Urban Life - Atkinson, Niall, 1967- (Book collections on Project MUSE., 2016)
"Analyzes how the premodern city, through the example of Renaissance Florence, can be understood as an acoustic phenomenon. Explores how city sounds, such as the ringing of church bells, can be foundational elements in the creation and maintenance of urban communities and the spaces they inhabit"--Provided by publisher.